Measurement of blood sugar and liver and kidney functions for newborns of diabetic pregnant famale mice fed therapeutic dairy (Texas Journal of Medical Science, 2022)
The study was conducted in the animal house of the College of Veterinary Medicine / Tikrit University and in the laboratories of the General Company for the Pharmaceutical Industry and Medical Appliances / Samarra for the period from October 2020 until the end of April 2021. It included the production of therapeutic yogurt with the addition of a mixture of probiotic supplements Lactobacillus Casei, Lb. planetarium, Lb. acidophilus and Bifidobacterium. Bifiduem) and a second starter of two types of probiotic (Bif. Bifiduem and Lb. casei) with some fruits (cranberry and strawberry) and therapeutic drugs (Gliclazide and Metformin), to know their effect on some physiological and biochemical parameters such as measuring blood sugar values, urea, creatinine, ALT, AST in female laboratory mice with diabetes Developed alloxan and fed on therapeutic dairy. The results showed that diabetic female rats in their newborns caused changes in glucose values, as there was a decrease in blood sugar values for 20-day-old babies (59.4) mg/dL and an increase in blood sugar values for 30-day-old babies, which amounted to (149.25) mg/dL, In addition, the values of urea (43) mL/dL, creatinine (1) mL/dL, AST and ALT enzymes (126.3 and 90.6) IU, and bilirubin (0.92 mg/dL) were measured.